Letters of tribulation - Francis, Pope, 1936-2025; Spadaro, Antonio; Fares, Diego, 1955- (Maryknoll : Orbis Books, 2020)
"Pope Francis draws on wisdom from Superiors General of the Jesuit order in the past to confront painful ordeals in the church today"--
Some letters written previously to being Pope.
Keywords: Francis, -- Pope, -- 1936-2025 -- Correspondence; Catholic Church -- History -- 1965-; Consolation; Personal correspondence